2017
DOI: 10.18203/2320-6012.ijrms20173966
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of periodontal health status among Koraga tribes residing in Mangalore taluk: a cross sectional study

Abstract: Background: To assess the periodontal health status among Koraga tribal community residing in Mangalore Taluk.Methods: The study subjects comprised of 400 Koraga tribal’s in the age range of 20-55 years living in Mangalore Taluk. The data regarding oral hygiene practices prevalent in the tribal population was collected by interviewing. Intra oral examination was carried out by using mouth mirror and CPI probe and included simplified oral hygiene index (OHI-S), community periodontal index (CPI), loss of attachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…al. [16] where 14.8% Koraga tribals had healthy gums. However, this was in contrast to that reported by Philip B et.…”
Section: Discussionmentioning
confidence: 99%
“…al. [16] where 14.8% Koraga tribals had healthy gums. However, this was in contrast to that reported by Philip B et.…”
Section: Discussionmentioning
confidence: 99%
“…All 256 study participants belonged to the sub-caste of Soligas. 16,17 In the current study, majority of the participants, 111 (43.5%) of them used smokeless form of tobacco. It was observed most commonly used products were betel leaves with arecanut powder.…”
Section: Discussionmentioning
confidence: 66%
“…This LOA score was less when compared to the current study. 5,10,16,21 When examined for oro-mucosal lesions, 228 (89.1%) of them did not have any abnormal condition, 3 (1.2%) had leukoplakia, 12 (4.7%) had ulceration and 12 (4.7%) had abscess. This was similar to the findings of the study conducted by Kumar et al among the Santhal tribes of Jharkhand where it was found that 784 (85.1%) participants were apparently healthy with no abnormal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tribes are more vulnerable to diseases and are less likely to utilize health services due to socioeconomic, cultural, and structural factors affecting the Gond community's access to oral health services. This is exacerbated by the limited knowledge of the necessary precautions to safeguard their well-being, individual beliefs and customs, their geographical remoteness from medical centers, the absence of dependable transport routes, and financial limitations [ 5 , 7 ]. According to Mooney, access is primarily determined by the availability of resources, whereas utilization is influenced by both the availability of resources and the level of demand.…”
Section: Introductionmentioning
confidence: 99%